Assessment of Groundwater Quality in Tha Xang Village, Pak Ngum district, Vientiane capital - KINGLATTANA, Latsamee; SILIBOUNTHAN, Somsanouk; KEOKHAMPHUI, Khaykeo; Pavelic, Paul; Banks, Eddie; Viossanges, Mathieu (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
Water resources are the main factor of livelihood and agricultural production, which is important for the Lao people as well as the study area. The study aimed to assess the quality of groundwater quality in Tha Xang village, Pak Ngum district, Vientiane capital and to assess the physical and chemical quality of groundwater. A total of 6 water samples were collected. The results of the study found that all 6 pH values ​​were lower than the national environmental standard set by the Ministry of Natural Resources and Environment (Lao PDR), and the value of HCO3- at each point is equal to zero. The values ​​of EC, TDS, Salinity, Turbidity, Total Hardness, SO42-, Cl-, F-, NO3-, K+), Na+, Mg2+, Ca2+, Fe, As, Cd. The results of the analysis was considered to be good quality due to the addition of water to the aquifer during the dry season from the irrigation system, The water is pumped into the aquifer and percolates through the soil and increases the amount of groundwater stored in the aquifer in the dry season. With pesticides, the analysis showed that the average values ​​of each groundwater well the same for all 6 wells, with the average values ​​being Chlorpyrifos with a value of <1.79 µg/L and Bifenthrin with a value of <1.81 µg/L. This shows that the amount of pesticides that are present in the groundwater may be a challenge in the future because in the Thang Xang village area, there is a cluster of villages that grow organic vegetables, This indicates that there is a tendency for pesticides to be present in groundwater sources and these may increase in the future. In particular, the amount of Facal Coliform Bacteria (FCB) in wells PTX05 and PTX06, the results of laboratory analysis showed that they exceeded the national environmental standards.